L’expertise profane dans la prise en charge hospitalière du VIH/SIDA au Cameroun : entre bénévolat et emploi - Fadimatou Mounsade Kpoundia (Anthropologie & Santé)
According to the Cameroonian National plan for the fight against AIDS, HIV patients should be associated to the therapeutic system in an HIV care center in order to provide psychological assistance to other HIV patients. They are accepted in the care process for their lay experience of HIV. They are volunteers from an association and are sometimes involved in therapy as workers. The aim of this study is to analyse how the lay expertise is mobilized in HIV care in hospitals. This study is based on ethnographic data collected in 5 regions in Cameroon, from interviews and observations of the professional practices of 193 people working in 15 hospitals and 26 associations fighting against HIV/AIDS.